Análisis comparativo del costo por estudiante de las Facultades Ciencias Empresariales y Ciencias de la Ingeniería de la Universidad Técnica Estatal de Quevedo y su incidencia en el presupuesto del año 2015 - Franco Cedeño, Flor Janet (2016)
The main objective of the research project entitled "Comparative analysis of the cost per student of the Faculties of Business Sciences and Faculty of Engineering Sciences of Quevedo State Technical University and their impact on the budget for 2015" was to analyze the cost per Student of the Faculty of Business Sciences and Faculty of Engineering Sciences and its impact on the budget of Quevedo State Technical University. Year 2015. The types of research that were used are: applied research, and documentary research; The research methods used were transactional descriptive, historical, inductive and deductive method. In the Faculty of Business Sciences total costs were $ 883646,76; While in the Faculty of Engineering Sciences the total cost was $ 720678.66. Unit costs per student were $ 1006.43 and $ 1563.29, respectively. The break-even point is 463 students for the Faculty of Engineering Sciences, the number of students who entered the 2011 cohort was 461 students, however, who finished the Curriculum in 2015, was a number Of 201 students. In the Faculty of Business Sciences the Point of Equilibrium is 881 which means that they are the students who should be graduated in the year 2015. However, the number of students who entered the Faculty was 878 and finished the Curriculum Network a Total of 265. The budget projection based on the demand for the Faculty of Engineering Sciences and Faculty of Business Sciences is for a total budget of $ 2380383,78. Key words.Costs, Budget, Student, Analysis